Increasing the Oral Bioavailability of Poorly Water-soluble Valsartan Using Non-ordered Mesoporous Silica Microparticles - Santosh, P. Bahirat (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To evaluate the use of mesoporous silica SYLOID® 244 FP to increase the dissolution rate of valsartan, antihypertensive poorly water soluble, Biopharmaceutical Classification System Class II drug. Materials and Methods: Valsartan was adsorbed on and/or into SYLOID® 244 FP in the ratio of 1:0.5, 1:1, and 1:1.5 via a wetness impregnation method and then processed into tablet by direct compression. To investigate the interaction in between valsartan and SYLOID® 244 FP, X-ray powder diffraction (XRPD) and Fourier transform infrared studies were performed. To examine the effect of SYLOID® 244 FP on the solubility of drug, phase solubility study was performed. Optimization of the study was done using 32 full factorial designs where amount of SYLOID® 244 FP (X1) and volume of ethanol (X2) were selected as independent variables and solubility and % cumulative release were selected as dependent variables. Flowability and wettability of the valsartan-loaded powder were evaluated by bulk and tapped density and by the angle of repose, respectively. Physical stability tests of the valsartan and the valsartan-SYLOID® 244 FP matrix were observed by keeping it over a 1-month storage at 40°C and 75% ± 5% humidity. Results and Discussion: The drug excipient interaction study revealed the absence of crystalline form and presence of hydrogen bonds interaction in valsartan-loaded powder. The improvement in the dissolution rate of tablet containing valsartan-loaded matrix is due to the lack of valsartan in the crystalline form and large surface area of the SYLOID® 244 FP. Satisfactory results of physical stability tests of the valsartan and the valsartan-SYLOID® 244 FP matrix were observed. Correspondingly, the solubility of the valsartan-loaded matrix was increased up to 2.83 times. Conclusion: Study indicates that valsartan tablet prepared from drug-loaded silica may provide a feasible approach for the development of an oral formulation for this poorly water-soluble drug.